The effect of the teacher-student relationship on the academic adjustment of returned migrant children: the chain mediating role of school attitude and resilience - Wang, Chuanyan (Frontiers in Psychology, 2025)
IntroductionReturned migrant children have not received widespread attention in China, and research on their academic adjustment is still limited. Teachers are important individuals who influence the academic development of returned migrant children, and the aim of the study is to analyze the mechanism by which the teacher-student relationship affects their academic adjustment.MethodsThis study followed a sample of 1921 returned migrant children across 8 counties in central and western China, using an academic adjustment scale, a teacher-student relationship scale, a school attitude scale, and a resilience scale. Pearson-moment correlations were used to analyze the the correlations among all variables, and the PROCESS macro (Model 6) in SPSS was used to examine the mediating effects.ResultsThe findings indicated that the teacher-student relationship significantly and positively predicted academic adjustment. Furthermore, the relationship indirectly influenced academic adjustment through school attitude and resilience, which acted as chain mediators.DiscussionThe findings highlight the importance of the teacher-student relationship in development outcomes. Moreover, early intervention and prevention efforts should be taken to improve their educational experience.